2003
DOI: 10.1128/mcb.23.24.9073-9080.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role Played by Microphthalmia Transcription Factor Phosphorylation and Its Zip Domain in Its Transcriptional Inhibition by PIAS3

Abstract: Mutation of microphthalmia transcription factor (MITF) results in deafness, bone loss, small eyes, and poorly pigmented eyes and skin. A search for MITF-associated proteins, using a mast cell library that was screened with a construct that encodes the basic helix-loop-helix leucine zipper (Zip) domain of MITF, resulted in the isolation of the STAT3 inhibitor, PIAS3. PIAS3 functions in vivo as a key molecule in suppressing the transcriptional activity of MITF. Here, we report that the Zip domain is the region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 46 publications
(47 reference statements)
2
49
0
Order By: Relevance
“…For instance, the ring finger domain has been shown to be important for PIAS3's activity as a sumo-E3 ligase (21,23). We have found that PIAS3 functions in vivo as a key molecule in suppressing the transcriptional activity of both MITF and STAT3 (10,24,25). More specifically, we demonstrated that following cellular activation, PIAS3 is released from MITF and binds to STAT3 (25).…”
mentioning
confidence: 72%
“…For instance, the ring finger domain has been shown to be important for PIAS3's activity as a sumo-E3 ligase (21,23). We have found that PIAS3 functions in vivo as a key molecule in suppressing the transcriptional activity of both MITF and STAT3 (10,24,25). More specifically, we demonstrated that following cellular activation, PIAS3 is released from MITF and binds to STAT3 (25).…”
mentioning
confidence: 72%
“…In the nucleus of resting cells, unphosphorylated Mitf is inactivated by association with PIAS3. Activation of the gp130 receptor or c-Kit receptor in melanoma and mast cells induces Mitf phosphorylation and results in the release of PIAS3, which then binds STAT3 (37,38). This indicates that the phosphorylation and dephosphorylation of Mitf is a key step in the regulation of interaction between Mitf, PIAS3, and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Within this fragment resides the Ser 409 residue; phosphorylation of this Ser 409 residue by RSK1 controls MITF targeting to proteasome (Wu et al 2000) and interaction with PIAS3 (Levy et al 2003).…”
Section: The Mitf C-terminal Domain Promotes Melanoma Cell Deathmentioning
confidence: 99%